RINT1 functions as a multitasking protein at the crossroads between genomic stability, ER homeostasis, and autophagy - Grigaravičius, Paulius; Deimling, Andreas von; Frappart, Pierre-Olivier (Autophagy, 2016)
RINT1 was first identified as an RAD50-interacting protein and its function was therefore linked to the maintenance of genomic stability. It was also shown that RINT1 was a key player in ER-Golgi trafficking as a member of an ER tethering complex interacting with STX18. However, due to early embryonic lethality of rint1-null mice, the in vivo functions of RINT1 remained for the most part elusive. We recently described the consequences of Rint1 inactivation in various neuronal cells of the central nervous system. We observed that lack of RINT1 in vivo triggers genomic instability and ER stress leading to depletion of the neural progenitor pool and neurodegeneration. Surprisingly, we also observed inhibition of autophagy in RINT1-deficient neurons, indicating an involvement of RINT1 in the regulation of neuronal autophagy. Here, we summarize our main RINT1 findings and discuss its putative roles in autophagy.